Peningkatan Hasil Panen Udang pada Budidaya Udang Tradisional di Desa Permisan Kecamatan Jabon Kabupaten Sidoarjo untuk Mengurangi Waktu Panen Menggunakan Metode Best Management Practice (BMP) [To Increases The Shrimp Harvesting in Traditional Shrimp Farmer in Permisan Village, Jabon District, Sidoarjo Region Losted Harvesting for a Long Time by Using Best Management Practise (BMP) Method] - Muhammad Arief; Gunanti Mahasri; Akhmad Taufiq Mukti (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Tiger Shrimp (Penaeus monodon Farb) is one of marine shrimps that have an important economically from fisheries sector. But since the end of 1993 up to now, there is high shrimp mortality that caused by the diseases andwater quality. It caused olmost the shrimp farmer lossed harvesting and due to this circumstance have been caused many ponds collapsed. The main objective of this societies service activities is applicated a new shrimp culture technology with traditional plus by using Best Management Practise (BMP), for increases the shrimp harvest at Permisan village, Region of Sidoarjo, it was done on May until October 2012. The method using in the activity were socialitation/counseling, dempond and guiding to application of the BMP Methode in one periode. Monitoring and evaluation about this result were done in one month after the activity ending. The result showed that a positive indication. There was the knowledges of the farmer in ceases by socialization, it also applicated a model in the right method for shrimp culture. There were also showed that the BMP Methode can inceased the shrimp harvest from 267 kg/ha to 903,652 kg/ha, it means was increased 276, %. The conclution of this activity is the BMP Methode can increased the shrimp harvest and can applicates in more larges area in Sidoarjo Region.